Preliminary in vivo characterization of a theranostic aptamer: Sgc8-c-DOTA-67 Ga. (2017) - Calzada, Victoria; , Jessica Báez; Sicco, Estefanía; Margenat, Jimena; Fernández, Marcelo; Moreno, María; Ibarra, Manuel; Quinn, Thomas; Gambini, Juan Pablo; Cabral, Pablo; Cerecetto, Hugo
No abstract available